2007 41st Annual Conference on Information Sciences and Systems 2007
DOI: 10.1109/ciss.2007.4298270
|View full text |Cite
|
Sign up to set email alerts
|

User Allocation in Multi-System, Multi-Service Scenarios: Upper and Lower Performance Bound of Polynomial Time Assignment Algorithms

Abstract: In this paper we cover the problem of how users of different service classes should be assigned to a set of radio access technologies (RAT). All RAT have overlapping coverage and the aim is to maximize a weighted sum of assignable users. Under the constraint that users cannot be split between multiple air-interfaces the problem is identified as NP-complete. In the first part of the paper we derive upper and lower bounds of polynomial assignment algorithms. Using Lagrangian theory and continuous relaxation we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…For this, the system is equipped with an heterogeneous access management (HAM) device which coordinates the resource sharing by following an admission control policy. For orthogonal air interfaces and for air interfaces where the resource costs depend only on the sum of interference and not on its compilation, this resource sharing problem can be formulated by associating a capacity value with each air interface and assigning to each user a set of cost values for the different air interfaces [1]. These cost values reflect the amount of resources required to support a user according to his requirements in a certain air interface.…”
Section: Introduction and Problem Formulationmentioning
confidence: 99%
“…For this, the system is equipped with an heterogeneous access management (HAM) device which coordinates the resource sharing by following an admission control policy. For orthogonal air interfaces and for air interfaces where the resource costs depend only on the sum of interference and not on its compilation, this resource sharing problem can be formulated by associating a capacity value with each air interface and assigning to each user a set of cost values for the different air interfaces [1]. These cost values reflect the amount of resources required to support a user according to his requirements in a certain air interface.…”
Section: Introduction and Problem Formulationmentioning
confidence: 99%
“…Reasons include different carrier frequencies and corresponding channel models of RATs, base station positioning, different interference situations and sensitivity to it. A concept that considers all earlier mentioned factors, like the system load, service class, interference situation, characteristics of the RAT, and users' positions, is the costbased approach, introduced and analyzed in [3,4]. There, it was observed that all characteristics can be bundled together in one cost parameter per user and RAT which suffice to calculate a close to optimum assignment that maximizes the total number of supportable voice users under static conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we analyze in which way users of different service classes should be assigned in a heterogeneous scenario, thereby extending ideas from [3,4]. Users request either a fixed minimum data rate, for example, as needed for voice services, or unconstrained best-effort (BE) data services.…”
Section: Introductionmentioning
confidence: 99%